Solid-state fermentation converts rice bran into a high-protein feed ingredient for Penaeus monodon - Huervana, Fredson H.; Traifalgar, Rex Ferdinand M.; Dionela, Cleresa S. (Frontiers in Marine Science, 2024)
Fermented rice bran (FRB) was evaluated as an alternative protein source to soybean meal (SM) in practical diets for juvenile black tiger shrimp, Penaeus monodon. This feed ingredient was tested in a feeding trial to replace soybean meal in P. monodon diets at 0% (T0), 12.5% (T12.5), 25% (T25), 37.5% (T37.5), and 50% (T50). Five iso-nitrogenous and iso-caloric experimental diets containing 44% crude protein were fed to groups of juvenile shrimp (0.47 ± 0.002 g) randomly assigned to twenty 60-l rectangular tanks equipped with a recirculating seawater system. Each dietary treatment was run in 4 replicates, and the feeding trial lasted 50 days. Results show significant improvement in weight gain, specific growth rate, and protein efficiency ratio in treatment T12.5 and T25. Treatments with higher levels of SM replacement with FRB exhibited similar growth indices to those of the control group. Polynomial regression analysis indicates that the optimum replacement of soybean meal with FRB for optimum growth is 21.08%. The apparent dry matter and protein digestibility coefficients of FRB are 83.05 ± 0.02% and 87.20 ± 0.30%, respectively. There were no significant differences in the whole-body composition (dry matter, protein, lipid, ash) among treatments of shrimp fed with FRB replacement. The data suggest that FRB replacement of dietary soybean meal is feasible at 50% without affecting the growth performance but may promote growth at 21.08% replacement of P. monodon.